Enhancing Broiler Feed Market Share in Jabodetabek: An Importance–Performance Analysis Approach - Fuad Dudin; Rahayu Widiyanti; Titin Widyastuti; Novie Andri Setianto; Ismoyowati (ANIMAL PRODUCTION, 2026)
This study aims to formulate a market share enhancement strategy for broiler feed in the Jabodetabek region using Importance-Performance Analysis (IPA). A survey was conducted with 68 PT NH customers in the Jabodetabek region as respondents. Data were analyzed using descriptive statistics and IPA. The results indicated that competitive pricing (Gap: +1.25), distribution availability (Gap: +1.20), and feed variety (Gap: +0.51) were the key priority attributes requiring improvement. In contrast, after-sales service, feed quality, and nutritional content were in the "Keep Up the Good Work" quadrant. The strategic recommendations derived from the IPA mapping include price restructuring through volume-based discounts and price matching guarantees, distribution network optimization through buffer stock points in Bekasi and Bogor with real-time inventory tracking, and product portfolio expansion through specialized formulations for different broiler growth phases. The implementation of these strategies, prioritizing resource reallocation from low-impact Quadrant D attributes (promotion programs) to critical Quadrant A attributes, is projected to increase market share by 15–20 percent through improved customer satisfaction while simultaneously reducing unnecessary promotional expenditures. This study fills three critical gaps in existing literature: (1) the absence of integrated multi-attribute analysis in feed marketing research, which has previously focused on single factors such as price or distribution in isolation; (2) the lack of attention to the unique logistical and operational characteristics of the Jabodetabek market, which differ fundamentally from other Indonesian regions; and (3) the limited attempts of previous studies to translate diagnostic IPA results into measurable, actionable implementation strategies with specific targets and timelines, rather than generic recommendations. The novelty of this research lies in its integration of IPA diagnostic results with concrete, time-bound strategic programs tailored specifically to the Jabodetabek context, combined with external market dynamics such as the 2026 soybean meal import policy shift and increasing competition from state-owned feed mills. Together, these contributions provide feed companies with a customer-centric, evidence-based framework for competitive positioning in Indonesia's most challenging poultry feed market.